Special interest councillors in Zimbabwean local authorities: challenges and opportunities - Mutema, Edson P.; Makanza, Virginia; Masiya, Tyanai (AFRICAN JOURNALS ONLINE, 2021)
This paper explores the challenges and opportunities of integrating special interest councilors in the governance of Zimbabwean local authorities. The study revealed that the current way in which special interest councilors are appointed in local authorities is an assault on local democracy. The process spruces up the policy making base of the political party to which the appointing minister belongs. However the study also reveals that despite the political challenges posed by the integration of special interest councilors in Zimbabwean local authorities at the moment, such appointments may be a progressive measure if done in a genuinely and transparent manner. It can bring critical skills which democracy may filter in favour of populism.